Beyond trade: The expanding scope of the non-trade agenda in trade agreements - Milewicz, K; Hollway, J; Peacock, C; Snidal, D (SAGE Publications, 2016)
Increased complexity and density of transnational problems creates unprecedented challenges and opportunities for contemporary international governance. ‘Issue linkage’ is one institutional arrangement through which states address these chang- ing circumstances. In this paper, we examine the widening scope of the non-trade agenda in Preferential Trade Agreements (PTAs). Non-trade issues (NTIs) such as human rights, democracy, environment, corruption and labor standards are increasingly linked to PTAs. This issue linkage has important implications for un- derstanding changing patterns of international trade, including the shift to PTAs and the rise of NTIs. We show that: (1) states’ choices to commit to bilateral or plurilateral versions of traditional PTAs and to PTAs with NTIs are highly interdependent; (2) states increasingly incorporate NTIs into PTAs as the associ- ated costs of policy change are lowered through earlier agreements and; (3) network pressures favor the increasing adoption of bilateral and especially plurilateral NTIs over time. Using an original data set on NTIs covering 522 PTAs and spanning the period 1951-2009, we evaluate states’ motives behind the widening non-trade agenda of trade agreements using longitudinal network modeling. We employ multiplex co-evolution stochastic actor-oriented network models (SAOMs) in a novel design to account for interdependencies within and across states’ decisions. Following a descriptive mapping of major non-trade issue areas, we evaluate our theoretical arguments. Testing against the alternative explanations of power and commitment, we find that endogenous cost considerations are the most significant factor explaining the inclusion of NTIs into PTAs.